1994
DOI: 10.1016/0378-1097(94)90526-6
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic desulfurization of dibenzothiophene by a cell-free system of Rhodococcus erythropolis D-1

Abstract: The enzymatic desulfurization of dibenzothiophene (DBT) to 2-hydroxybiphenyl (2-HBP) was detected in extracts of Rhodococcus erythropolis D-1 grown on DBT as a sole source of sulfur. In the dialyzed cell-free extracts, NADH was absolutely required for the activity. DBT desulfurization proceeded linearly with the reaction time, and stoichiometric amounts of 2-HBP were finally formed. The activity was stimulated by increasing the protein and NADH concentrations up to 5 mg ml-1 and 5 mM, respectively, when 0.1 mM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…del Olmo et al 2005a;Ohshiro and Izumi 1999;Kilbane and Jackowski 1992;Honda et al 1998;Guchhait et al 2005). Concerning to the operation modes, aerobic BDS conversion can be carried out by growing cells Honda et al 1998;Guchhait et al 2005), free cell extracts (Ohshiro et al 1994) and also resting cells (Ohshiro et al 1999;Gallagher et al 1993;Oldfield et al 1997;Maghsoudi et al 2001;Jia et al 2006;Luo et al 2002). The highest DBT conversion levels reported in literature has been achieved with resting cells (Ohshiro et al 1996;Konishi et al 1997).…”
Section: Introductionmentioning
confidence: 89%
“…del Olmo et al 2005a;Ohshiro and Izumi 1999;Kilbane and Jackowski 1992;Honda et al 1998;Guchhait et al 2005). Concerning to the operation modes, aerobic BDS conversion can be carried out by growing cells Honda et al 1998;Guchhait et al 2005), free cell extracts (Ohshiro et al 1994) and also resting cells (Ohshiro et al 1999;Gallagher et al 1993;Oldfield et al 1997;Maghsoudi et al 2001;Jia et al 2006;Luo et al 2002). The highest DBT conversion levels reported in literature has been achieved with resting cells (Ohshiro et al 1996;Konishi et al 1997).…”
Section: Introductionmentioning
confidence: 89%
“…It has been reported that some bacteria utilize DBT as a sole source of sulfur without breaking its carbon-carbon backbone. This sulfur-specific pathway has been extensively studied by using two Rhodococcus strains, Rhodococcus erythropolis IGTS8 (7,11,13) and R. erythropolis D-1 (10,19,20). The genes encoding enzymes involved in this pathway have been cloned and sequenced in R. erythropolis IGTS8 (2,3,25) and the thermophilic desulfurizing bacterium Paenibacillus sp.…”
mentioning
confidence: 99%
“…The authors further reported that from 1992 until 2017, many strains of Rhodococcus sp followed the 4S pathway. These include, for example, R. erythropolis D-1 (Ohshiro, Hine, & Izumi,1994), R. erythropolis H-2 (Ohshiro et al,1994), and Rhodococcus sp. ECRD-1 (Grossman et al, 2001), R. globerulus DAQ3 (Yang et al, 2007), R. erythropolis DRA (Q.…”
Section: Aerobic Desulfurizing Bacteriamentioning
confidence: 99%
“…For example, Rhodococcus sp IGTS8 was utilized on dibenzothiophene as a sole sulfur source in coal and crude oil (Kilbane & Bielaga, 1990;Nekodzuka et al, 1997). Here, the isolated Rhodococcuc erythropolis D-1 has been shown to selectively remove sulfur by oxidizing dibenzothiophene (Ohshiro et al, 1994). A similar study reported that the R. erythropolis H-2 was capable of attacking the sulfur atoms in 3,4-benzo DBT, 2,8-dimethy DBT, and 4,6-dimethyl DBT (Ohshiro et al, 1996), while the Rhodococcus erythropolis SHT87 completely desulfurized DBT (Davoodi-Dehaghani et al, 2010).…”
Section: Model Compounds For Biodesulfurization Systemsmentioning
confidence: 99%